Pretext for Religious Violence in Indonesia: An Anthropolinguistic Analysis of Fatwas on Ahmadiyya - Fariz Alnizar (Studia Islamika, 2019)
This study uses an anthropolinguistic approach to examine two Majelis Ulama Indonesia (MUI) fatwa texts regarding Ahmadiyya. First, it shows that there are significant differences between the 1980 and 2005 fatwas. Second, in terms of their lexicon, the 1980 fatwa uses the phrase "di luar Islam" (outside Islam), while the 2005 fatwa uses the phrase "berada di luar Islam" (located outside Islam). Third, there is an emphasis on the responsibilities of the government within the 2005 fatwa on Ahmadiyya. Fourth, the 1980 fatwa was directed at the Qadiyan Ahmadiyya, while the 2005 fatwa was directed at all elements of Ahmadiyya. Fifth, the form of the 2005 fatwa is reminiscent of a legal proclamation. This strongly affected the violence experienced by Ahmadiyya, as the fatwa was no longer presented as an opinion, but as a legally binding decision.